Diabetic hand syndrome: case reports - Miranda-Manrique, Gonzalo (2024)
Diabetic hand syndrome is a rare and underdiagnosed complication of diabetes mellitus. This term is used to describe a potentially dangerous infection of the hand, characterized by debilitating musculoskeletal disorders. Although the diagnosis is commonly made in tropical regions, cases have also been reported in non-tropical and in marginal urban areas. The pathophysiology of this syndrome remains unclear because, unlike diabetic foot, peripheral neuropathy and vascular disease do not seem to a play major role. Evidence suggests that it may be associated with the duration of diabetes, poor metabolic control and microvascular complications. In this article, we present the cases of two patients with diabetic hand syndrome. The first case involves a 52-year-old female patient from a rural area, diagnosed with type 2 diabetes mellitus six years ago, currently in poor metabolic control. She underwent amputation of the fourth finger with a favorable postoperative course. The second case involves a 60-year-old male patient from a marginal urban area in Lima, also diagnosed with type 2 diabetes mellitus. He underwent amputation of the left second finger with a surgical diagnosis of necrosis and tenosynovitis. Diabetic hand syndrome can have a significant clinical impact and may lead to permanent disability. Early diagnosis improves prognosis, thus the importance of performing thorough physical examinations of the hands in patients with diabetes mellitus.